Subject-Oriented Business Process Management - Fleischmann, Albert; Schmidt, Werner; Stary, Christian; Obermeier, Stefan; Börger, Egon (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Activities performed in organizations are coordinated according to organizational goals via communication between the people involved. In all known languages the sentences used to communicate  are naturally  structured by subject, verb, and object. The subject  describes the actor, the verb the action and the object what is affected by the action.  Subject-oriented Business Process Management (S-BPM) as presented in this book is based on this simple structure which enables  process-oriented thinking  and process modeling. S-BPM puts the subject of a process at the center of attention and thus deals with business processes and their organizational environment from a new perspective, meeting organizational requirements in a much better way than traditional approaches. Subjects represent agents of an action in a process,  which can be either technical or human (e.g. a thread in an IT system or a clerk). A process structures the actions of each subject and coordinates the required communication among the subjects. S-BPM provides a coherent procedural framework to model an organization's business processes: its focus is the cooperation of all stakeholders involved in the strategic, tactical, and operational issues, sharing their knowledge in a networked structure. Based on findings of developmental psychology and linguistics, the authors show that natural sentence semantics have to be used for complete S-BPM specifications. In this way, business process owners are able to ensure that business requirements of internal and external stakeholders are easily understood and met in their entirety. Starting with process analysis and then going through the whole modeling lifecycle, they demonstrate how subject orientation can develop and be experienced by gradually focusing on communication for service provision. In addition, they illustrate how each modeling activity can be supported through the use of appropriate software tools. The authors' presentation style focuses on professionals in the industry, and on students specializing in process management or organizational modeling.  Each chapter begins with a summary of key findings and is full of examples, hints, and possible pitfalls. An interpreter model, a toolbox, and a glossary summarizing the main terms complete the book. The web site www.i2pm.net provides additional software tools and further material.